Mediator analysis of psychological empowerment: reverse causality with strategic HRM dimensions and firm performance. (1st January 2013) - Bhatnagar, Jyotsna
This study attempts to clarify the mediating role of psychological empowerment on organisational commitment in the relationship between strategic human resource (HR) roles and organisational learning capability, and the impact of these strategic human resource management (HRM) dimensions on organisations' performance. Using a sample of 640 Indian managers, this study demonstrates that psychological empowerment is an important mediator only when there is a reverse causality between firm performance and strategic HR roles in the Indian context. The structural equation models applied to the data reflected models of moderate fit. This study makes possible contributions to the black-box debate in strategic HRM that is discussed with implications for theory and practice.